Method for stripping two-dimensional material through ionic liquid and nanocellulose intercalation
Through the separation method of ionic liquid and nanocellulose, the problems of low yield and impurity introduction in the preparation of two-dimensional materials in the prior art are solved, and high-quality and low-cost large-scale production is achieved, and the crystal integrity of the nanosheets is retained. , suitable for the application expansion of two-dimensional materials.
Patent Information
- Application Number
- CN202411450642.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-13
AI Technical Summary
The existing two-dimensional material preparation technology has problems such as low yield, easy introduction of impurities, high equipment costs, and strict selection of precursors, which limits the application of two-dimensional materials in large-scale production and high-quality preparation.
Using the method of peeling the ionic liquid and nanocellulose, the wood material is heated and stirred with choline chloride, lactic acid, oxalic acid and other substances at high temperature to form nanocellulose and disperse it with the ionic liquid, and is shaken by mechanical stirring and ultrasonic vibration. The supernatant rich in thin layer two-dimensional material was obtained, centrifuged and dried to obtain a large-sized thin layer two-dimensional material.
It realizes the preparation of two-dimensional materials with simple operation, high product quality and low cost, retains the crystal integrity of the nanosheets, avoids the damage to the structure by solvent treatment, and is suitable for large-scale production.
Smart Images

Figure CN119118074A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of two-dimensional material preparation, and relates to a method for preparing two-dimensional materials by liquid phase exfoliation, and specifically to a method for exfoliating two-dimensional materials by intercalation of ionic liquid and nanocellulose. Background Art
[0002] As an emerging nanomaterial, two-dimensional materials are only a few atomic layers thick and exhibit unique electronic, optical and mechanical properties, thus showing great application potential in electronics, optoelectronics, energy storage and sensor technology. With the deepening of the understanding of the properties and application potential of two-dimensional materials, a variety of preparation techniques have been developed, each with its own unique advantages and limitations. Mechanical exfoliation is one of the earliest methods used to prepare graphene. Its principle is to exfoliate single or multiple layers of two-dimensional materials from bulk materials by mechanical exfoliation or exfoliation. The advantages of this method include simplicity, no need for complex equipment, and the ability to obtain high-quality materials. However, the process of mechanical exfoliation is uncontrollable, resulting in low yield and easy introduction of impurities or defects, which limits its application in large-scale production. Chemical vapor deposition is a method of growing two-dimensional material films by pyrolyzing volatile precursors on metal substrates. Compared with mechanical exfoliation, CVD can grow two-dimensional materials uniformly on large-area substrates and has a high degree of controllability, which can adjust the thickness and composition of the materials. However, CVD requires high temperature and a specific atmosphere, high equipment cost, and strict requirements on the selection and treatment of precursors. It is easily affected by impurities, which limits its application in the preparation of high-quality two-dimensional materials. The liquid phase exfoliation method obtains single-layer or multi-layer two-dimensional materials by chemically or physically exfoliating the bulk material in a solvent. Compared with the first two methods, liquid phase exfoliation has a relatively low cost, is suitable for large-scale production, and can be operated under a wider range of conditions. However, the selection of solvents is demanding, which can easily affect the quality and structure of the material, and impurities may be introduced during the exfoliation process. The preparation technology of two-dimensional materials is constantly evolving, and with the increasing demand for new material performance, its application field will be further expanded. By optimizing existing technologies and exploring new preparation methods, two-dimensional materials are expected to become an important part of future nanotechnology and materials science, promoting the development of technology and innovation in applications. Summary of the invention
[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for exfoliating two-dimensional materials by intercalation of ionic liquids and nanocellulose, which is simple to operate and has higher product quality.
[0004] In order to achieve the above object, the present invention adopts the following technical solutions:
[0005] A method for exfoliating a two-dimensional material by intercalation of an ionic liquid and nanocellulose comprises the following steps:
[0006] Step 1: encapsulate the wood material, choline chloride, lactic acid, oxalic acid and deionized water in a sealed container and heat and stir at 200-250° C. for 30-40 minutes, then add distilled water, sodium chlorite and acetic acid to the mixed solution for bleaching, and filter and wash the mixed solution to obtain nanocellulose;
[0007] Wherein, by weight, the amount of wood material is 8 to 10 parts, the amount of choline chloride is 40 to 50 parts, the amount of lactic acid is 20 to 30 parts, the amount of oxalic acid is 10 to 20 parts, the amount of deionized water is 10 to 20 parts, the amount of distilled water is 400 to 500 parts, the amount of sodium chlorite is 10 to 15 parts, and the amount of acetic acid is 5 to 10 parts;
[0008] Step 2: Dispersing the nanocellulose in deionized water and adding an ionic liquid, stirring the mixture mechanically to form a uniform dispersion, transferring the dispersion into a sealed container, and allowing it to stand at 200-250° C. for 300-600 minutes to obtain a standby dispersion;
[0009] Wherein, in parts by weight, the amount of nanocellulose is 5 to 10 parts, the amount of deionized water is 200 to 300 parts, and the amount of ionic liquid is 10 to 20 parts;
[0010] Step 3: Dispersing the bulk layered crystal material in the standby dispersion obtained in step 2 and homogenizing the dispersion, transferring the homogenized dispersion into a sealed container, and allowing the sealed container containing the dispersion to stand at 150-180° C. for 300-600 min and at 200-240° C. for 300-600 min, respectively, to obtain a mixed dispersion;
[0011] Wherein, by weight, the amount of bulk layered crystal material is 5 to 10 parts, and the amount of standby dispersion liquid is 50 to 80 parts;
[0012] Step 4: Separate the mixed dispersion into a clean container and subject it to a tip ultrasonic oscillation treatment for 60 to 120 minutes, then let it stand for 20 to 24 hours to obtain a supernatant rich in thin-layer two-dimensional materials. Centrifuge, dry, and grind the obtained supernatant to obtain large-sized thin-layer two-dimensional materials.
[0013] The present invention also has the following technical features:
[0014] Preferably, the wood material in step 1 comprises a mixture of one or more materials selected from poplar wood powder, corn straw powder, Chinese fir powder, Scotch pine powder, and wood cellulose.
[0015] Preferably, the bleaching treatment in step 1 is to heat and stir the mixed solution at 90-100° C. for 4-6 hours.
[0016] Preferably, the ionic liquid described in step 2 includes any one of 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-octyl-3-methylimidazolium hexafluorophosphate and 1-ethyl-3-methylimidazolium ethanesulfonate.
[0017] Preferably, the bulk layered crystal material described in step three includes any one of graphite, molybdenum disulfide, molybdenum diselenide, boron nitride, and graphite fluoride.
[0018] Preferably, the power of the tip ultrasonic oscillation treatment described in step 4 is 1000-1200W.
[0019] Preferably, the drying in step 4 is drying in an oven at 60° C. for 12 hours.
[0020] Compared with the prior art, the present invention has the following technical effects:
[0021] The raw materials used in the present invention are cheap, and the natural wood raw materials used have the advantages of being green, environmentally friendly and pollution-free. The deconstruction of wood materials and the extraction of nano-cellulose can be quickly achieved through improved solvent treatment means, and ionic liquid (ILs) molecules are creatively grafted onto the surface of nano-cellulose. Through the restriction effect of the nano-cellulose network on the two-dimensional material, the ILs molecules are quickly promoted to be inserted into the interlayer of the two-dimensional material under a hydrothermal environment, and while achieving uniform dispersion of the two-dimensional material, the embedding of ILs molecules and nano-cellulose into the interlayer and the increase of the interlayer spacing are greatly promoted. This intercalation and stripping method can not only retain the crystal integrity of the two-dimensional material nanosheet to a large extent, but also avoid the damage to the structure of the two-dimensional material during the solvent treatment process due to the protection mechanism of cellulose, and can obtain large-sized two-dimensional material nanosheets of micrometer size.
[0022] The method of the invention is easy to operate, takes less time, and has higher product quality, thus promoting the research, development and application of cellulose-assisted intercalation stripping technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a TEM image of cellulose modified with ILs prepared in Example 1;
[0024] Figure 2 is a TEM image of the hexagonal boron nitride nanosheets prepared in Example 1;
[0025] Figure 3 is a TEM image of graphene prepared in Example 2;
[0026] Figure 4 This is the XRD spectrum of the characteristic peak of graphene (002) prepared in Example 2. DETAILED DESCRIPTION
[0027] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0028] Example 1
[0029] A method for exfoliating a two-dimensional material by intercalation of ionic liquid and nanocellulose, the preparation method comprising the following steps:
[0030] Step 1, 8 kg of poplar wood powder, 40 kg of choline chloride, 20 kg of lactic acid, 10 kg of oxalic acid and 10 kg of deionized water are packaged in a sealed container and heated and stirred at 200 ° C for 30 minutes, then 400 kg of distilled water, 10 kg of sodium chlorite and 5 kg of acetic acid are added to the mixed solution and heated and stirred at 90 ° C for 4 hours, and the mixed solution is filtered and washed with water to obtain nanocellulose;
[0031] Step 2: Disperse 5 kg of nanocellulose in 200 kg of deionized water and add 10 kg of 1-butyl-3-methylimidazolium tetrafluoroborate, and stir the mixture mechanically to form a uniform dispersion. Transfer the dispersion to a sealed container and allow it to stand at 200° C. for 300 min to obtain a standby dispersion.
[0032] Step 3: Disperse 5 kg of hexagonal boron nitride in 50 kg of the standby dispersion obtained in step 2 and homogenize the dispersion, transfer the dispersion into a sealed container, and place the sealed container containing the dispersion at 150° C. for 300 min and at 200° C. for 300 min, respectively, to obtain a mixed dispersion;
[0033] Step 4: Separate the mixed dispersion into a clean container and subject it to tip ultrasonic oscillation treatment (1000W) for 60 minutes. Then, let the mixed dispersion stand for 20 hours to obtain a supernatant rich in thin-layer two-dimensional materials. Centrifuge the obtained supernatant, then dry it in an oven at 60°C for 12 hours, and grind it in a mortar for 15 minutes to obtain large-sized thin-layer two-dimensional materials.
[0034] Example 2
[0035] A method for exfoliating a two-dimensional material by intercalation of ionic liquid and nanocellulose, the preparation method comprising the following steps:
[0036] Step 1: 10 kg corn stalk powder, 50 kg choline chloride, 30 kg lactic acid, 20 kg oxalic acid and 20 kg deionized water are packaged in a sealed container and heated and stirred at 250° C. for 30 min, then 500 kg distilled water, 15 kg sodium chlorite and 10 kg acetic acid are added to the mixed solution and heated and stirred at 100° C. for 6 hours, and the mixed solution is filtered and washed with water to obtain nanocellulose;
[0037] Step 2: Disperse 10 kg of nanocellulose in 300 kg of deionized water and add 20 kg of 1-ethyl-3-methylimidazolium chloride, stir the mixture mechanically to form a uniform dispersion, transfer the dispersion to a sealed container, and allow it to stand at 250° C. for 600 min to obtain a standby dispersion;
[0038] Step 3: Disperse 10 kg of graphite in 80 kg of the standby dispersion obtained in step 2 and homogenize the dispersion, transfer the dispersion into a sealed container, and place the sealed container containing the dispersion at 180° C. for 600 min and at 240° C. for 600 min, respectively, to obtain a mixed dispersion;
[0039] Step 4: Separate the mixed dispersion into a clean container and subject it to tip ultrasonic oscillation treatment (1200W) for 120 minutes. Then, let the mixed dispersion stand for 24 hours to obtain a supernatant rich in thin-layer two-dimensional materials. Centrifuge the obtained supernatant, then dry it in an oven at 60°C for 12 hours, and grind it in a mortar for 15 minutes to obtain large-sized thin-layer two-dimensional materials.
[0040] Example 3
[0041] A method for exfoliating a two-dimensional material by intercalation of ionic liquid and nanocellulose, the preparation method comprising the following steps:
[0042] Step 1, 3 kg of lignocellulose powder, 45 kg of choline chloride, 25 kg of lactic acid, 15 kg of oxalic acid and 20 kg of deionized water are packaged in a sealed container and heated and stirred at 250° C. for 40 min, then 450 kg of distilled water, 13 kg of sodium chlorite and 8 kg of acetic acid are added to the mixed solution and heated and stirred at 100° C. for 5 hours, and the mixed solution is filtered and washed with water to obtain nanocellulose;
[0043] Step 2: Disperse 10 kg of nanocellulose in 250 kg of deionized water and add 15 kg of 1-butyl-3-methylimidazolium tetrafluoroborate, and stir the mixture mechanically to form a uniform dispersion. Transfer the dispersion to a sealed container and allow it to stand at 250° C. for 500 min to obtain a standby dispersion.
[0044] Step 3: Disperse 8 kg of molybdenum disulfide in 70 kg of the standby dispersion obtained in step 2 and homogenize the dispersion, transfer the dispersion into a closed container, and allow the closed container containing the dispersion to stand at 160° C. for 500 min and at 220° C. for 500 min, respectively, to obtain a mixed dispersion;
[0045] Step 4: Separate the mixed dispersion into a clean container and subject it to tip ultrasonic oscillation treatment (1000W) for 100 minutes. Then, let the mixed dispersion stand for 22 hours to obtain a supernatant rich in thin-layer two-dimensional materials. Centrifuge the obtained supernatant, then dry it in an oven at 60°C for 12 hours, and grind it in a mortar for 15 minutes to obtain large-size thin-layer two-dimensional materials.
[0046] Example 4
[0047] A method for exfoliating a two-dimensional material by intercalation of ionic liquid and nanocellulose, the preparation method comprising the following steps:
[0048] Step 1: 10 kg of fir powder, 40 kg of choline chloride, 22 kg of lactic acid, 18 kg of oxalic acid and 20 kg of deionized water are packaged in a sealed container and heated and stirred at 250° C. for 35 minutes, then 400 kg of distilled water, 13 kg of sodium chlorite and 8 kg of acetic acid are added to the mixed solution and heated and stirred at 95° C. for 5 hours, and the mixed solution is filtered and washed with water to obtain nanocellulose;
[0049] Step 2: 8 kg of nanocellulose is dispersed in 300 kg of deionized water and 15 kg of 1-octyl-3-methylimidazolium hexafluorophosphate is added, the mixture is mechanically stirred to form a uniform dispersion, the dispersion is transferred to a sealed container, and allowed to stand at 220° C. for 450 min to obtain a standby dispersion;
[0050] Step 3: Disperse 10 kg of graphite fluoride in 70 kg of the standby dispersion obtained in step 2 and homogenize the dispersion, transfer the dispersion into a sealed container, and place the sealed container containing the dispersion at 180° C. for 500 min and at 240° C. for 600 min to obtain a mixed dispersion;
[0051] Step 4: Separate the mixed dispersion into a clean container and subject it to tip ultrasonic oscillation treatment (1100W) for 120 minutes. Then, let the mixed dispersion stand for 24 hours to obtain a supernatant rich in thin-layer two-dimensional materials. Centrifuge the obtained supernatant, then dry it in an oven at 60°C for 12 hours, and grind it in a mortar for 15 minutes to obtain large-sized thin-layer two-dimensional materials.
[0052] Example 5
[0053] A method for exfoliating a two-dimensional material by intercalation of ionic liquid and nanocellulose, the preparation method comprising the following steps:
[0054] Step 1, 9 kg of Scotch pine wood powder, 40 kg of choline chloride, 25 kg of lactic acid, 20 kg of oxalic acid and 18 kg of deionized water are packaged in a sealed container and heated and stirred at 240° C. for 35 minutes, then 500 kg of distilled water, 13 kg of sodium chlorite and 8 kg of acetic acid are added to the mixed solution and heated and stirred at 95° C. for 5 hours, and the mixed solution is filtered and washed with water to obtain nanocellulose;
[0055] Step 2: Disperse 10 kg of nanocellulose in 300 kg of deionized water and add 15 kg of 1-ethyl-3-methylimidazolium ethanesulfonate, stir the mixture mechanically to form a uniform dispersion, transfer the dispersion to a sealed container, and allow it to stand at 200° C. for 450 minutes to obtain a standby dispersion;
[0056] Step 3: Disperse 10 kg of molybdenum diselenide in 80 kg of the standby dispersion obtained in step 2 and homogenize the dispersion, transfer the dispersion into a sealed container, and place the sealed container containing the dispersion at 180° C. for 600 min and at 240° C. for 600 min to obtain a mixed dispersion;
[0057] Step 4: Separate the mixed dispersion into a clean container and subject it to tip ultrasonic oscillation treatment (1200W) for 120 minutes. Then, let the mixed dispersion stand for 24 hours to obtain a supernatant rich in thin-layer two-dimensional materials. Centrifuge the obtained supernatant, then dry it in an oven at 60°C for 12 hours, and grind it in a mortar for 15 minutes to obtain large-sized thin-layer two-dimensional materials.
[0058] Figure 1 is the TEM image of ILs modified cellulose prepared in Example 1. Figure 1 It can be seen that cellulose can reach nanoscale size and retain its original morphology without structural damage;
[0059] Figure 2 is a TEM image of the hexagonal boron nitride nanosheets prepared in Example 1. Figure 2 It can be seen that as the exfoliation continues, the hexagonal boron nitride nanosheets have a large lateral size of micrometer level and a very thin layer structure, and maintain relatively complete crystal structure characteristics;
[0060] Figure 3 is a TEM image of graphene prepared in Example 2. Figure 1It can be seen that before stripping, nanocellulose is evenly distributed around graphite, forming a good network and limiting the range of graphite activity in the liquid phase, ensuring that it does not undergo significant sedimentation. The graphene produced after stripping has a large lateral size of several microns, and the surface is covered with ionic liquid functionalized nanocellulose inserted between its layers, and the corresponding crystal diffraction pattern shows that it has high crystal integrity and crystallinity;
[0061] Figure 4 is the XRD spectrum of the characteristic peak of graphene (002) prepared in Example 2, Figure 1 It can be seen that the obvious shift of the characteristic peak of graphene before and after exfoliation further proves the increase in the graphene interlayer spacing, which shows that the technology of nanocellulose and ionic liquid intercalation exfoliation of two-dimensional materials is feasible, and the intercalation of the two in the two-dimensional material layer frame is the intrinsic reason for its exfoliation effect.
[0062] Although the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention.
Claims
1. A method for exfoliating two-dimensional materials by intercalation of ionic liquids and nanocellulose, It is characterized in that The following steps are involved: Step 1: encapsulate the wood material, choline chloride, lactic acid, oxalic acid and deionized water in a sealed container and heat and stir at 200-250° C. for 30-40 minutes, then add distilled water, sodium chlorite and acetic acid to the mixed solution for bleaching, and filter and wash the mixed solution to obtain nanocellulose; Wherein, by weight, the amount of wood material is 8 to 10 parts, the amount of choline chloride is 40 to 50 parts, the amount of lactic acid is 20 to 30 parts, the amount of oxalic acid is 10 to 20 parts, the amount of deionized water is 10 to 20 parts, the amount of distilled water is 400 to 500 parts, the amount of sodium chlorite is 10 to 15 parts, and the amount of acetic acid is 5 to 10 parts; Step 2: Dispersing the nanocellulose in deionized water and adding an ionic liquid, stirring the mixture mechanically to form a uniform dispersion, transferring the dispersion into a sealed container, and allowing it to stand at 200-250° C. for 300-600 minutes to obtain a standby dispersion; Wherein, in parts by weight, the amount of nanocellulose is 5 to 10 parts, the amount of deionized water is 200 to 300 parts, and the amount of ionic liquid is 10 to 20 parts; Step 3: Dispersing the bulk layered crystal material in the standby dispersion obtained in step 2 and homogenizing the dispersion, transferring the homogenized dispersion into a sealed container, and allowing the sealed container containing the dispersion to stand at 150-180° C. for 300-600 min and at 200-240° C. for 300-600 min, respectively, to obtain a mixed dispersion; Wherein, by weight, the amount of bulk layered crystal material is 5 to 10 parts, and the amount of standby dispersion liquid is 50 to 80 parts; Step 4: Separate the mixed dispersion into a clean container and subject it to a tip ultrasonic oscillation treatment for 60 to 120 minutes, then let it stand for 20 to 24 hours to obtain a supernatant rich in thin-layer two-dimensional materials. Centrifuge, dry, and grind the obtained supernatant to obtain large-sized thin-layer two-dimensional materials.
2. The method for exfoliating two-dimensional materials by intercalation of ionic liquid and nanocellulose as claimed in claim 1, It is characterized in that The wood material described in step 1 includes a mixture of one or more materials selected from poplar wood powder, corn straw powder, Chinese fir powder, Scotch pine powder, and wood cellulose.
3. The method for exfoliating two-dimensional materials by intercalation of ionic liquid and nanocellulose as claimed in claim 1, It is characterized in that The bleaching treatment in step 1 is specifically to heat and stir the mixed solution at 90-100° C. for 4-6 hours.
4. The method for exfoliating two-dimensional materials by intercalation of ionic liquid and nanocellulose as claimed in claim 1, It is characterized in that The ionic liquid described in step 2 includes any one of 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-octyl-3-methylimidazolium hexafluorophosphate and 1-ethyl-3-methylimidazolium ethanesulfonate.
5. The method for exfoliating two-dimensional materials by intercalation of ionic liquid and nanocellulose as claimed in claim 1, It is characterized in that The bulk layered crystal material described in step three includes any one of graphite, molybdenum disulfide, molybdenum diselenide, boron nitride, and graphite fluoride.
6. The method for exfoliating two-dimensional materials by intercalation of ionic liquid and nanocellulose as claimed in claim 1, It is characterized in that The power of the tip ultrasonic vibration treatment described in step 4 is 1000-1200W.
7. The method for exfoliating two-dimensional materials by intercalation of ionic liquid and nanocellulose as claimed in claim 1, It is characterized in that The drying described in step 4 is drying in an oven at 60° C. for 12 hours.
Citation Information
Patent Citations
Green sustainable cellulose-based lubricant and preparation method thereof
CN116396793A
